Highly efficient inverted organic photovoltaics using solution based titanium oxide as electron selective contact - Choulis, Stelios A.; Waldauf, Christoph; Morana, Mauro (My University, 2006)
The challenge to reversing the layer sequence of organic photovoltaics (OPVs) is to prepare a selective contact bottom cathode and to achieve a suitable morphology for carrier collection in the inverted structure. The authors report the creation of an efficient electron selective bottom contact based on a solution-processed titanium oxide interfacial layer on the top of indium tin oxide. The use of o -xylene as a solvent creates an efficient carrier collection network with little vertical phase segregation, providing sufficient performance for both regular and inverted solar cells. The authors demonstrate inverted layer sequence OPVs with AM 1.5 calibrated power conversion efficiencies of over 3%
Keywords: Photovoltaic cells; Electrons; Morphology; Solar cells; Titanium oxides